On the comprehensibility and perceived privacy protection of indirect questioning techniques - Hoffmann, Adrian; Waubert de Puiseau, Berenike; Schmidt, Alexander F.; Musch, Jochen (Behavior research methods, 2017)
On surveys that assess sensitive personal attributes, indirect questioning aims at increasing respondents’ willingness to answer truthfully by protecting confidentiality. However, the assumption that subjects understand questioning procedures fully and trust them to protect their privacy is rarely tested. In a scenario-based design, we compared four indirect questioning procedures in terms of their comprehensibility and perceived privacy protection. All indirect questioning techniques were found to be less comprehensible by respondents than a conventional direct question used for comparison. Less-educated respondents experienced more difficulties when confronted with any indirect questioning technique. Regardless of education, the crosswise model was found to be the most comprehensible among the four indirect methods. Indirect questioning in general was perceived to increase privacy protection in comparison to a direct question. Unexpectedly, comprehension and perceived privacy protection did not correlate. We recommend assessing these factors separately in future evaluations of indirect questioning.